ANALISIS INOVASI PEMASARAN MELALUI LIVE STREAMING TIK TOK DALAM MENARIK MINAT CALON JAMA’AH HAJI DAN UMROH DI PT NUR HARAMAIN - Zainullah, Ahmad; Ulfi, Diana; Aqidah, Waqi’atul (Jurnal Ekonomi dan Bisnis (EK&BI), 2025)
This study aims to analyze marketing innovation through TikTok live streaming in attracting the interest of prospective Hajj and Umrah pilgrims at PT Nur Haramain Mulia. The research employs a descriptive qualitative approach with data collected through interviews, observations, and documentation. The findings indicate that TikTok Live has a positive impact on enhancing engagement with prospective pilgrims, building trust, and expanding market reach. The live broadcasts typically feature explanations of travel packages, customer testimonials, and special promotions delivered in an interactive manner. This marketing approach also contributes to shaping a modern and responsive corporate image. Nevertheless, the implementation faces several challenges, including limited human resources skilled in managing digital content, unstable internet connections, and low digital literacy among older audiences. Despite these obstacles, with ongoing improvements, live streaming-based digital marketing holds significant potential to support the growth of Hajj and Umrah travel services in a more efficient, adaptive, and sustainable manner.